Modified polyether-ether-ketone material for spaceflight pyrotechnic device and preparation method of modified polyether-ether-ketone material

By introducing functional groups such as phenolphthalein and potassium hydroquinone sulfonate into PEEK materials, the modified polyether ether ketone sulfonocyanide copolymer PEEK-NS is solved, and the problem of insufficient material performance in aerospace fire equipment is improved. The sealing performance is improved and processing performance meets the high temperature and high pressure requirements of aerospace thermal equipment.

CN119306941AActive Publication Date: 2025-01-14CHUANNAN MACHINERY PLANT CHINA ASTRONAUTIC SCI &TECH GROUP CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411544153.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-14
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing PEEK materials cannot meet the performance requirements of compression, sealing and high temperature resistance in aerospace thermal equipment, and have insufficient processing performance, especially in extreme environments, showing a problem of reduced sealing.

Method used

By introducing functional groups such as phenolphthalein and potassium hydroquinone sulfonate, the modified polyether ether ketone sulfonocyanide copolymer PEEK-NS is synthesized through nucleophilic polycondensation reaction, which improves the mechanical strength, temperature resistance and metal compatibility of the material and improves the mechanical strength, temperature resistance and metal compatibility of the material. Liquidity.

Benefits of technology

It improves the sealing performance of aerospace thermal equipment, can be used for a long time in extreme environments, meets high sealing requirements, and shows better fluidity during injection molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306941A_ABST
    Figure CN119306941A_ABST
Patent Text Reader

Abstract

The invention provides a modified polyether-ether-ketone material for a spaceflight pyrotechnic device and a preparation method of the modified polyether-ether-ketone material, and the modified polyether-ether-ketone material is prepared by polymerizing 4, 4-difluorobenzophenone, 2, 6-dichlorobenzonitrile, phenolphthalein and hydroquinone potassium sulfonate. The molar ratio of the 4, 4-difluorobenzophenone to the 2, 6-dichlorobenzonitrile to the phenolphthalein to the hydroquinone potassium sulfonate is (1.5-4.5): (10-14): (3.5-6.5): (8-12), and the sum of the amount of substance of the 4, 4-difluorobenzophenone and the amount of substance of the 2, 6-dichlorobenzonitrile is equal to the sum of the amount of substance of the phenolphthalein and the amount of substance of the hydroquinone potassium sulfonate. By introducing functional groups, the mechanical strength, temperature resistance and pressure resistance of the PEEK material are improved, and the interfacial compatibility of the PEEK material and a metal material is improved, so that the sealing performance of a spaceflight pyrotechnic device is improved, and the flowability of the PEEK is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof. Background Art

[0002] With the increasing number of aerospace missions such as the launch of high-orbit satellites and the operation and maintenance of space stations in orbit, pyrotechnic devices are required to be able to withstand extreme environments such as extremely high temperatures, extremely low temperatures, large temperature differences, and solar radiation. Some of its structures have high requirements for the material's pressure resistance, sealing, insulation, and high temperature resistance. It is difficult for conventional materials to take into account the above properties at the same time. In particular, the non-metallic materials currently used in some parts, such as glass fiber-modified phenolic resin, generally show low heat resistance and impact resistance, and the processing method has defects such as high energy consumption and high pollution. In addition, when applied to the sealing structure of the pyrotechnic device, the high temperature and impact coupling conditions generated after the product works may induce a decrease in the product's sealing, making it difficult for the product to meet the high sealing requirements after ignition.

[0003] Polyarylether polymers are typical representatives of currently commercialized thermoplastic special engineering plastics, among which polyetheretherketone (PEEK) is the most eye-catching. PEEK refers to a polymer composed of repeating units containing one ketone bond and two ether bonds in the main chain structure. It is a linear aromatic polymer compound with a large number of benzene rings. It has excellent processing properties and is easy to be injection molded, extruded and cut. It is one of the top special engineering plastics with the best comprehensive performance. PEEK has been widely used in cutting-edge fields such as aerospace, electronic information, medical equipment, and nuclear power generation. Especially in the field of aerospace, PEEK can replace aluminum and other metal materials to manufacture aircraft parts, and its weight can be reduced by up to 70% compared with metal. In addition, the European Space Agency cooperated with the Portuguese polymer engineering company PIEP to launch a 3D printed PEEK material three-dimensional small satellite product, which successfully passed commercial tests. At the same time, PEEK injection molded radomes, fasteners, aerospace fuel tanks and other parts have gradually become mainstream products in the industry.

[0004] Although polyarylether special polymer materials have been successfully applied in the aerospace field, their application in the field of aerospace pyrotechnics, known as the "heart of thermal weapons", is still in its infancy. In limited non-critical applications, polyarylether raw materials (such as PEEK, PEI, etc.) and finished products from foreign companies are generally used, and the degree of independent control is low. At the same time, the existing PEEK materials still need to be modified in order to meet the performance requirements of pyrotechnics for pressure resistance, sealing, insulation and high temperature resistance.

[0005] Therefore, it is necessary to design a formula to meet the requirements of aerospace pyrotechnics for the ability to withstand extreme environments such as extremely high temperatures, extremely low temperatures, large temperature differences, and solar radiation, and to solve the problem of limited application of existing PEEK materials in aerospace pyrotechnics, mainly as follows:

[0006] (1) The metal compatibility of pure PEEK material cannot meet the airtightness requirements when used in aerospace pyrotechnic devices.

[0007] (2) The mechanical strength of pure PEEK material cannot meet the temperature and pressure resistance requirements of aerospace pyrotechnic devices at the moment of ignition.

[0008] (3) Pure PEEK material has insufficient fluidity during injection molding when used in aerospace pyrotechnics. Summary of the invention

[0009] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof. By introducing functional groups, the mechanical strength, temperature resistance and pressure resistance of the PEEK material are improved, the interface compatibility between the PEEK material and the metal material is improved, thereby improving the sealing performance of the aerospace pyrotechnic device and improving the fluidity of PEEK.

[0010] The technical solution provided by the present invention is as follows:

[0011] In the first aspect, a method for preparing a modified polyetheretherketone material is provided, wherein phenolphthalein and potassium hydroquinone sulfonate are used as phenol sources, and 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile are combined to synthesize a polyetheretherketone sulfonyl cyanide copolymer PEEK-NS modified material with cyano and sulfonic acid groups through a nucleophilic polycondensation reaction. The method comprises:

[0012] Mixing 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, potassium hydroquinone sulfonate, a catalyst and an organic solvent in a reactor;

[0013] The reaction system is heated to carry out polycondensation reaction to synthesize a crude modified polyetheretherketone material;

[0014] The crude modified polyetheretherketone material is purified to obtain the purified modified polyetheretherketone material.

[0015] In a second aspect, a modified polyetheretherketone material is prepared by polymerizing 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, and potassium hydroquinone sulfonate;

[0016] The molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate is (1.5-4.5):(10-14):(3.5-6.5):(8-12), and the sum of the amounts of 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile is equal to the sum of the amounts of phenolphthalein and potassium hydroquinone sulfonate.

[0017] A modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof provided by the present invention have the following beneficial effects:

[0018] (1) The present invention provides a modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof, using phenolphthalein and potassium hydroquinone sulfonate as phenol sources, wherein phenolphthalein has a twisted non-planar structure and has a large steric hindrance, so that the copolymer does not crystallize, and has better fluidity during injection molding, thereby solving the problem of insufficient fluidity of pure PEEK during injection molding of aerospace pyrotechnic devices with complex structures;

[0019] (2) The present invention provides a modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof. A sulfonic acid group is introduced in the synthetic modification by potassium hydroquinone sulfonate. The sulfonic acid group is a polar group and is easy to graft. When used, it can be connected to other interfaces to improve the interface compatibility, thereby solving the problem of insufficient sealing performance caused by low interface compatibility of pure PEEK when used in aerospace pyrotechnic devices. The modified aerospace pyrotechnic devices are tested for sealing performance by the bubble method and can meet the sealing requirement of 29.5MPa / 1min without air leakage, while pure PEEK material can only meet the sealing requirement of 19MPa / 1min without air leakage. The phenolic resin modified with glass fiber can meet the requirement of 25MPa / 1min without air leakage for aerospace pyrotechnic devices, but it is difficult to meet the requirement of 29MPa / 1min for aerospace pyrotechnic devices for manned spaceflight.

[0020] (3) The present invention provides a modified polyetheretherketone material for aerospace pyrotechnic devices and a preparation method thereof. A cyano group is introduced during the synthesis. When heated, the cyano group can cross-link with other groups to form a network structure, which helps to improve the temperature resistance. The glass transition temperature is about 236°C and can be used for a long time within the range of 300°C. At the same time, the cyano group has a large steric hindrance, which also helps to improve the fluidity during processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of synthesis of a method for modifying PEEK material for aerospace pyrotechnics device of the present invention;

[0022] Figure 2 is an infrared spectrum of the modified PEEK material prepared in Example 1 of the present invention;

[0023] Figure 3is a DSC curve diagram of the modified PEEK material prepared in Example 1 of the present invention;

[0024] Figure 4 is a TGA curve diagram of the modified PEEK material prepared in Example 1 of the present invention;

[0025] Figure 5 This is a graph showing the change in the intrinsic viscosity of the modified PEEK material prepared in Example 1 of the present invention over time. DETAILED DESCRIPTION

[0026] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0027] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0028] The present invention provides a method for modifying a polyetheretherketone material, comprising the following steps:

[0029] Step 1: 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, potassium hydroquinonesulfonate (potassium 2,5-dihydroxybenzenesulfonate), a catalyst and an organic solvent are mixed in a reactor. In this step, 2,6-difluorobenzonitrile can also be used instead of 2,6-dichlorobenzonitrile.

[0030] In this step, the molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate is (1.5-4.5):(10-14):(3.5-6.5):(8-12), and the sum of the amounts of 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile is equal to the sum of the amounts of phenolphthalein and potassium hydroquinone sulfonate.

[0031] Preferably, the molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate is (2-4):(11-13):(4-6):(9-11), and the sum of the amounts of 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile is equal to the sum of the amounts of phenolphthalein and potassium hydroquinone sulfonate.

[0032] More preferably, the molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate is (2.5-3.5):(11.5-12.5):(4.5-5.5):(9.5-10.5), such as 3:12:5:10, and the sum of the amounts of 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile is equal to the sum of the amounts of phenolphthalein and potassium hydroquinone sulfonate.

[0033] In this step, the catalyst is selected from potassium carbonate (K 2 CO 3 ), sodium carbonate (Na 2 CO 3 ), preferably potassium carbonate (K 2 CO 3 ).

[0034] In this step, the organic solvent includes a first solvent and a second solvent, the first solvent is selected from at least one of polar aprotic solvents such as N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethylacetamide (DMAc), sulfolane, etc., and the second solvent is selected from a combination of at least one of toluene and xylene, such as a combination of NMP and toluene. Preferably, the volume ratio of the first solvent to the second solvent is (2 to 4): 1, such as 3: 1.

[0035] In this step, the total mass ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate to the mass ratio of the catalyst and the organic solvent is 70:(25-50):(80-140), such as 70:32:99.

[0036] Step 2: After assembling a water separation device on the reactor, the reaction system is heated to carry out a prepolymerization reaction. During the reaction, the generated water is separated until the dehydration is completed. The reaction rate is accelerated by continuously separating the generated water in the system.

[0037] In this step, the reactor is equipped with a thermometer, an agitator and a water separator. The reaction is accompanied by stirring and the reaction temperature is monitored during the reaction. The water separator includes a water separator and a condenser. The water separator containing an appropriate amount of toluene and the condenser connected to cold water are installed on the reaction device and sealed before starting the condensation reaction.

[0038] In this step, the prepolymerization temperature is 150-160°C, such as 155°C.

[0039] Step 3, heating the reaction system to carry out polycondensation reaction to synthesize the crude modified polyetheretherketone material. The synthesis schematic diagram is shown in Figure 1 .

[0040] In this step, the polycondensation reaction temperature is 185-190° C., and the reaction time is 1-4 hours.

[0041] Step 4: purify the crude modified polyetheretherketone material to obtain purified modified polyetheretherketone material (PEEK-NS).

[0042] In this step, the purification process is as follows:

[0043] Step 4.1, pouring the crude modified polyetheretherketone material cooled to a suitable temperature (100-120° C.) into anhydrous ethanol for precipitation hardening for more than 12 hours;

[0044] Step 4.2, in order to remove the unreacted raw material monomers and catalysts, the precipitate is crushed, and then washed with reflux heating and stirring in an acidic aqueous solution (mass fraction 5% to 10%) for more than 2 hours, the temperature (80 to 100°C), and the acidic aqueous solution is a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution or a nitric acid aqueous solution. Then the crushed precipitate is washed with a volatile organic solvent and hot water in sequence, preferably acetone, ethanol, and hot water in sequence, acetone and ethanol washing for at least 10 minutes each, hot water washing twice, each time for at least 0.5 hours, and finally the product is placed in an oven at 100 to 130°C, such as 120°C, and dried for at least 4 hours.

[0045] The present invention also provides a modified polyetheretherketone material, which is prepared by the polyetheretherketone material modification method described above.

[0046] Example

[0047] Example 1

[0048] A method for modifying PEEK material for aerospace pyrotechnic devices comprises the following steps:

[0049] Step 1: First, fix a 250mL three-necked flask equipped with a thermometer and a stirrer on a heating mantle, and weigh the raw materials and solvent (NMP + toluene) in proportion and add them into the three-necked flask in sequence. The molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, and potassium hydroquinone sulfonate is: 0.03mol: 0.12mol: 0.05mol: 0.1mol, K 2 CO 3 The total weight of the crude product was 31.8 g, the total weight of NMP was 75 mL, and the total weight of toluene was 25 mL.

[0050] Step 2: Start stirring, raise the temperature to 155°C, and perform reflux dehydration. Observe the dehydration condition. After the dehydration is completed, gradually raise the temperature to 190°C, continue stirring and reacting for 2 hours. Figure 5 It can be seen that the intrinsic viscosity is relatively stable after 2 hours of reaction, indicating that the polycondensation reaction is complete and a high molecular weight product PEEK-NS is synthesized.

[0051] Step 3: Pour the synthesized product cooled to 120°C into anhydrous ethanol for precipitation and hardening for 12 hours, and then crush the precipitated product using a crusher to remove the unreacted raw material monomers and K 2 CO 3The crushed product is also washed with reflux heating and stirring in a mixed solution of water and hydrochloric acid (mass fraction 8%) for 2 hours, and then washed and filtered with acetone, ethanol and hot water in turn, washing with acetone and ethanol for 10 minutes each, and washing with hot water twice, each time for 0.5 hours. After washing and filtering, the product is placed in an oven at 120°C and dried for 4 hours.

[0052] The infrared spectrum of PEEK-NS prepared in Example 1 is shown in Figure 2 It can be seen that PEEK-NS contains sulfonic acid groups (530cm -1 、1190cm -1 ) and cyano (2231cm -1 ) characteristic peak; DSC curve diagram see Figure 3 , it can be seen that the glass transition temperature of PEEK-NS is 236°C. In addition, the melting point of PEEK-NS is 355°C, the viscosity is 3.1dL / g, the melt index at 400°C is 83g / 10min, the tensile strength is 121.8MPa, the flexural modulus is 3.31GPa, and the elongation at break is 11.2%. The 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 553℃ and 564℃ respectively, showing excellent thermal stability. Figure 4 .

[0053] The PEEK-NS prepared in Example 1 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 29.5 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was less than 1×10 - 8 Pa·m 3 / s, the sealing performance and ignition performance meet the requirements.

[0054] Examples 2 to 3 and Comparative Examples 1 to 4

[0055] A method for modifying PEEK material for aerospace pyrotechnic devices comprises the following steps:

[0056] Step 1: First, fix a 250mL three-necked flask equipped with a thermometer and a stirrer on a heating mantle, and weigh the raw materials and solvent (NMP + toluene) according to the proportion and add them into the three-necked flask in sequence. The molar ratios of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, and potassium hydroquinone sulfonate in Examples 2 to 3 and Comparative Examples 1 to 4 are shown in Table 1, K 2 CO 3 The total weight of the crude product was 31.8 g, the total weight of NMP was 75 mL, and the total weight of toluene was 25 mL.

[0057] Table 1 Raw material ratio

[0058] Example / Comparative Example 4,4-Difluorobenzophenone 2,6-Dichlorobenzonitrile Phenolphthalein Potassium Hydroquinone Sulfonate Example 1 0.03 0.12 0.05 0.10 Example 2 0.02 0.11 0.04 0.09 Example 3 0.04 0.13 0.06 0.11 Comparative Example 1 0.01 0.14 0.05 0.10 Comparative Example 2 0.06 0.09 0.05 0.10 Comparative Example 3 0.03 0.12 0.02 0.13 Comparative Example 4 0.03 0.12 0.08 0.07

[0059] Step 2: Start stirring and raise the temperature to 155°C for reflux dehydration. Observe the dehydration condition here. After the dehydration is completed, gradually raise the temperature to 190°C and continue stirring the reaction for 2 hours. The high molecular weight product modified PEEK is synthesized by polycondensation reaction.

[0060] Step 3: Pour the synthesized product cooled to 120°C into anhydrous ethanol for hardening and precipitation for 12 hours, and then crush the precipitated product using a crusher to remove the unreacted raw material monomers and K 2 CO 3 The crushed product is also washed with reflux heating and stirring in a mixed solution of water and hydrochloric acid (mass fraction 8%) for 2 hours, and then washed and filtered with acetone, ethanol and hot water in turn, washing with acetone and ethanol for 10 minutes each, and washing with hot water twice, each time for 0.5 hours. After washing and filtering, the product is placed in an oven at 120°C and dried for 4 hours.

[0061] The results of Example 2 are as follows:

[0062] The PEEK-NS prepared in Example 2 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm -1 ), a glass transition temperature of 238°C, a melting point of 359°C, a viscosity of 3.2 dL / g, a melt index of 80 g / 10 min at 400°C, a tensile strength of 119.3 MPa, a flexural modulus of 3.32 GPa, an elongation at break of 10.8%, and a 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 554℃ and 564℃ respectively, showing excellent thermal stability.

[0063] The PEEK-NS prepared in Example 2 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 27.3 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was less than 1×10 - 8 Pa·m 3 / s, the sealing performance and ignition performance meet the requirements.

[0064] The results of Example 3 are as follows:

[0065] The PEEK-NS prepared in Example 3 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm-1 ) characteristic peak, and the glass transition temperature is 228°C. In addition, the melting point of PEEK-NS is 348°C, the viscosity is 2.9dL / g, the melt index at 400°C is 88g / 10min, the tensile strength is 118.8MPa, the flexural modulus is 3.23GPa, the elongation at break is 11.5%, and the 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 531℃ and 546℃ respectively, showing excellent thermal stability.

[0066] The PEEK-NS prepared in Example 3 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 27.8 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was less than 1×10 - 8 Pa·m 3 / s, the sealing performance and ignition performance meet the requirements.

[0067] The results of Comparative Example 1 are as follows:

[0068] The PEEK-NS prepared in Comparative Example 1 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm -1 ) characteristic peak, and the glass transition temperature is 202°C. In addition, the melting point of PEEK-NS is 325°C, the viscosity is 2.6dL / g, the melt index at 400°C is 92g / 10min, the tensile strength is 92.5MPa, the flexural modulus is 2.84GPa, the elongation at break is 8.5%, and the 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 489℃ and 501℃ respectively, showing excellent thermal stability.

[0069] The PEEK-NS prepared in comparative example 1 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 22 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was greater than 1×10 -8 Pa·m 3 / s, the sealing performance and ignition performance do not meet the requirements.

[0070] The results of Comparative Example 2 are as follows:

[0071] The PEEK-NS prepared in Comparative Example 2 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm-1 ) characteristic peak, and the glass transition temperature is 212°C. In addition, the melting point of PEEK-NS is 332°C, the viscosity is 2.7dL / g, the melt index at 400°C is 90g / 10min, the tensile strength is 98.9MPa, the flexural modulus is 2.99GPa, the elongation at break is 9.3%, and the 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 503℃ and 515℃ respectively, showing excellent thermal stability.

[0072] The PEEK-NS prepared in comparative example 2 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 21 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was greater than 1×10 -8 Pa·m 3 / s, the sealing performance and ignition performance do not meet the requirements.

[0073] The results of Comparative Example 3 are as follows:

[0074] The PEEK-NS prepared in Comparative Example 3 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm -1 ) characteristic peak, and the glass transition temperature is 223°C. In addition, the melting point of PEEK-NS is 338°C, the viscosity is 2.7dL / g, the melt index at 400°C is 55g / 10min, the tensile strength is 111.2MPa, the flexural modulus is 3.02GPa, the elongation at break is 9.5%, and the 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 528℃ and 539℃ respectively, showing excellent thermal stability.

[0075] The PEEK-NS prepared in comparative example 3 was injected into a metal insert and installed in an aerospace pyrotechnic device. Due to its poor fluidity and poor surface quality, the sealing performance was 15Mpa / 1min without leakage. After the high and low temperature cycle test, it was ignited by heat preservation. The leakage rate of the helium mass spectrometer leak test was greater than 1×10 -8 Pa·m 3 / s, the sealing performance and ignition performance do not meet the requirements.

[0076] The results of Comparative Example 4 are as follows:

[0077] The PEEK-NS prepared in Comparative Example 4 contains sulfonic acid groups (530 cm -1 、1190cm -1 ) and cyano (2231cm-1 ) characteristic peak, and the glass transition temperature is 227°C. In addition, the melting point of PEEK-NS is 342°C, the viscosity is 2.8dL / g, the melt index at 400°C is 88g / 10min, the tensile strength is 102.3MPa, the flexural modulus is 3.06GPa, the elongation at break is 10.3%, and the 5% thermal decomposition temperature (T 5% ) and 10% thermal decomposition temperature (T 10% ) exceeded 522℃ and 531℃ respectively, showing excellent thermal stability.

[0078] The PEEK-NS prepared in Comparative Example 4 was injected into a metal insert and installed in an aerospace pyrotechnic device. The sealing performance was 17 MPa / 1 min without leakage. After the high and low temperature cycle test, the heat preservation ignited. The helium mass spectrometer leak detection showed that the leakage rate was greater than 1×10 -8 Pa·m 3 / s, the sealing performance and ignition performance do not meet the requirements.

[0079] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0080] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A modified polyetheretherketone material, characterized in that: Prepared by polymerization of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate; The molar ratio of 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate is (1.5-4.5):(10-14):(3.5-6.5):(8-12), and the sum of the amounts of 4,4-difluorobenzophenone and 2,6-dichlorobenzonitrile is equal to the sum of the amounts of phenolphthalein and potassium hydroquinone sulfonate.

2. A method for preparing a modified polyetheretherketone material, characterized in that: include: Mixing 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein, potassium hydroquinone sulfonate, a catalyst and an organic solvent in a reactor; The reaction system is heated to carry out polycondensation reaction to synthesize a crude modified polyetheretherketone material; The crude modified polyetheretherketone material is purified to obtain the purified modified polyetheretherketone material.

3. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The catalyst is selected from at least one of potassium carbonate (K2CO3) and sodium carbonate (Na2CO3).

4. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The organic solvent includes a first solvent and a second solvent, the first solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethylacetamide (DMAc), and sulfolane, and the second solvent is selected from a combination of at least one of toluene and xylene.

5. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The volume ratio of the first solvent to the second solvent is (2-4):

1.

6. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The mass ratio of the total mass of the 4,4-difluorobenzophenone, 2,6-dichlorobenzonitrile, phenolphthalein and potassium hydroquinone sulfonate to the mass ratio of the catalyst and the organic solvent is 70:(25-50):(80-140).

7. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: Before the reaction system is heated to carry out polycondensation reaction and the crude modified polyetheretherketone material is synthesized, the method further includes: heating the reaction system to carry out prepolymerization reaction, and separating the water generated during the reaction until dehydration is completed.

8. The method for preparing the modified polyetheretherketone material according to claim 7, characterized in that: The prepolymerization temperature is 150-160°C.

9. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The polycondensation reaction temperature is 185-190°C.

10. The method for preparing the modified polyetheretherketone material according to claim 2, characterized in that: The step of purifying the crude modified polyetheretherketone material comprises: The crude modified polyetheretherketone material after cooling is poured into anhydrous ethanol for precipitation hardening; The precipitate is crushed, washed with an acidic aqueous solution, an organic solvent and hot water in sequence, and dried to obtain a purified modified polyetheretherketone material.

Citation Information

Patent Citations

  • Method for preparing polyaromatic ether by utilizing liquid phase pulverization

    CN113388103A

  • Semi-crystalline biphenyl copolymerized polyether-ether-ketone resin and preparation method thereof

    CN116515101A

  • Manufacturing method of ionic group-containing polymer, ionic group-containing polymer obtained by the same, and application for polyelectrolyte film containing ionic group-containing polymer, or the like

    JP2008037895A